DESCRIPTION OF COVID-19 MANAGEMENT FOR PREGNANT MOTHERS IN PAGENTAN PUBLIC HEALTH CENTER 2 BANJARNEGARA REGENCY - Lia Aria Ratmawati; Ratih Subekti (Siklus : Journal Research Midwifery Politeknik Tegal, 2021)
During pandemic COVID-19, pregnant women were included in the susceptible group. Although, there has been no evidence of reports of vertical transmission from mother to fetus. COVID-19 prevention and control guidelines have been prepared and referred to WHO guidelines and government laws and regulations. This study aimed to describe COVID-19 management for pregnant women at the Pagentan Public Health Center 2, Banjarnegara Regency. This research used a descriptive method with a cross-sectional approach—the data used were secondary data from the medical report on the COVID-19 screening of pregnant women. Data analysis used univariate analysis. The number of samples was 36 respondents. The results showed that the swab test conducted on 36 respondents resulted in 5 respondents (13.9%) were positive, and 31 respondents (86.1%) were negative. Management of pregnant women with covid-19 was self-isolation at home, education on strengthening health protocols, and increasing endurance. A follow-up swab test was carried out again after the 14th day, and all respondents' results are negative. Keywords: Management, Pregnant Women, Covid-19